2010
DOI: 10.4141/cjps10014
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of RAPD and ISSR markers in assessing genetic diversity and relationships in black gram (Vigna mungo L. Hepper) vari

Abstract: , W. 2010. Efficiency of RAPD and ISSR markers in assessing genetic diversity and relationships in black gram (Vigna mungo L. Hepper) varieties. Can. J. Plant Sci. 90: 443Á452. The DNA fingerprinting methodologies, random amplified polymorphic DNA (RAPD) and inter-simple sequence repeat (ISSR), were used to estimate genetic diversity and relationships among 20 black gram (Vigna mungo L. Hepper) varieties. Thirty selected RAPD primers amplified 255 bands, 168 of which were polymorphic (66.5%). On average, these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…The ISSR primers employed in the present study afforded 79.23% polymorphism and, therefore, could be considered very efficient at determining the variability in C. argentea. The level of polymorphism reported herein is similar to values obtained for other leguminous species such as Vigna mungo (Kanimozhi et al, 2009;Karuppanapandian et al, 2010), Arachis hypogaea (Mondal et al, 2009), and Caragana microphylla (Huang et al, 2013), but higher than those reported by Souframanien and Gopalakrishna (2004) for V. mungo (54.5%) and by Muthusamy et al (2008) for V. umbellata (61.78%).…”
Section: Discussionsupporting
confidence: 89%
“…The ISSR primers employed in the present study afforded 79.23% polymorphism and, therefore, could be considered very efficient at determining the variability in C. argentea. The level of polymorphism reported herein is similar to values obtained for other leguminous species such as Vigna mungo (Kanimozhi et al, 2009;Karuppanapandian et al, 2010), Arachis hypogaea (Mondal et al, 2009), and Caragana microphylla (Huang et al, 2013), but higher than those reported by Souframanien and Gopalakrishna (2004) for V. mungo (54.5%) and by Muthusamy et al (2008) for V. umbellata (61.78%).…”
Section: Discussionsupporting
confidence: 89%
“…Although iso-zyme and protein markers are useful for characterizing genetic diversity and identifying hybrids of cultivars (Das and Mukarjee 1995;De Vries 1996), the paucity of isozyme and protein methodologies restrict their usefulness in breeding analysis. Molecular markers have been applied widely in genetic analyses and breeding studies, as well as investigations of genetic diversity and relationships between cultivated species (Karuppanapandian et al, 2010). The Randomly Amplified Polymorphic DNA (RAPD) technique (Williams et al, 1990;Hadrys et al, 1992) amongst the PCR based methods has been most popular because of speed, low cost and the use of minute amount of plant material for analysis.…”
Section: Introductionmentioning
confidence: 99%
“…For proofing of different genotypes, classification of several varieties and diversity estimation in crops like Green Gram, (Karuppanapandian et al, 2006) and Black Gram (Karuppanapandian et al, 2007), RAPD marker technique has been extensively used (Fig. 1-3 and Table 6).…”
Section: Polymorphism In Triticum Species Using Rapd Primersmentioning
confidence: 99%